PEMBUATAN DAN PENGUJIAN VISKOSITAS DAN DENSITAS BIODIESEL DARI BEBERAPA JENIS MINYAK JELANTAH - Irawati, A. (JFT: Jurnal Fisika dan Terapannya, 2018)
This research attempts to know the quality of biodisel based on measurements of physics. Using five sample of biodisel from several species of cooking oil, there are fortune, sedaap, cemara, coconut oil and panah mas. method that performed on this research is by applying the measurement of a density of mass and viscosity. Based on the results obtained density of mass from sedaap type are 0,8 gr/ml, (fulfill the value standard 0,88 gr/ml), while for other biodisel was not fullfill to the value standard, viscosity discharging 1 times with temperature 40 °C ( 0,0610; 0,0362; 0,0359; 0,0515 and 0,0513). So biodisel sedaap fulfill the ISO standard while the value of viscosity discharging twice not much different from the use of 1 times namely sample biodisel b (sedaap) and the other was not far different with sedaap . Keywords: jelantah oil, biodisel, viscosity, density of mass